Mestno okolje, njegove nevarnosti in človeško vedenje - Polič, Marko (Urbani izziv, 1999)
The physical environment is only a tool, a medium or a place enabling human interrelations to develop. This is perhaps the most evident in cases of dangers people confront within an environment. Everything from disasters and minor incidents to vandalism and crime is reflected in human behaviour, from satisfying our basic needs all the way to discerning the sense of reality. The article presents an array of reflections from accidents and dangers in an urban environment, then can hurt the largest number of people, to less dangerous, but unpleasant acts for an individual.
Keywords: bivalno okolje; crime; ecology; ekologija; ekološka psihologija; kriminal; kvaliteta življenja; mesta; nesreče; security; urbana sociologija; varnost